(untitled) (Research, Society and Development, 2025)
Objective: To describe the experience of educational activities in first aid, with an emphasis on CPR, developed by nursing professors and aimed at high school students, with a focus on strengthening citizenship. Methodology: This is an experience report based on workshops on first aid, with an emphasis on CPR, for high school students. Results: Each workshop lasted 30 minutes with an average participation of 70 students per group. In total, 540 high school students participated with their respective teachers. The main weaknesses identified were related to assessing the safety of the environment, recognizing the appropriate time to call emergency services, and identifying the signs of cardiopulmonary arrest. Conclusion: The experience demonstrated the relevance of first aid education, especially in teaching CPR, as a strategy to strengthen the culture of safety and citizenship in the school environment.